A Comparison of Sound Levels in Open Plan Versus Pods in a Neonatal Intensive Care Unit. (April 2017) - Ramm, Karlie; Mannix, Trudi; Parry, Yvonne; Gaffney, Mary P. (Caroline)
Objective: The objective of this study was to compare the noise levels recorded in two different neonatal intensive care unit (NICU) settings: a pod and an open plan NICU located in the same hospital. Background: The NICU is a busy environment with ambient noise levels that often exceed established recommendations. This noise deleteriously affects the physiological stability and developmental outcomes of sick and preterm infants. Pods have reduced numbers of cots (in this case, 6) compared to open plan NICUs (in this case, 11), yet the noise levels in pods have not been reported. Method: This study compared real-time decibel (dB) levels in an A-weighted scale, captured continuously by sound dosimeters mounted in both NICU settings for a period of 4 weeks: a pod setting and an open plan NICU. Researchers also collected observational data. Results: The average noise level recorded in the pod was 3 dBs less than in the open plan NICU. This result was statistically significant. However, dB recordings in both areas were over the recommended limits by 4–6 dBs, with isolated peaks between 74.5 dBs (NICU) and 75.9 dBs (pod). Observational data confirmed this correlation. Conclusions: Further research to evaluate interventions to decrease the noise levels in both settings are needed, especially during times of peak activity. Staff working in these settings need to be more aware that control of acoustic levels is important in the neuroprotection of neonates. Coupling this with careful consideration to structural components and evidence-based design planning may contribute to lowering dB levels in the NICU environment.